Studies of functional properties of espin 1: Its interaction to actin filaments - Yang, Jeong Bin; Kim, Kwang Sub; Heo, Jiwon; Chung, Jeong Min; Jung, Hyun Suk (Frontiers in Cell and Developmental Biology, 2022)
Actin is a multifunctional biomolecule that forms not only basic structural bodies such as filopodia and lamellipodia, but also large microvilli-like organelles like stereocilia. Actin consists of four sub-domains (S1, S2, S3, and S4), and the “target-binding groove” formed between S1 and S3 is the major binding site for various actin binding proteins. Actin filament dynamics are regulated by numerous actin binding proteins with different mechanisms of actin binding, assembly, and disassembly such as actin severing, branching, and bundling. Ectoplasmic specialization protein 1 (espin 1) is an actin binding and bundling protein that is specifically implicated in the elongation and stabilization of stereocilia as a binding partner with myosin III. However, little is known about the molecular structure, actin bundling, and stabilizing mechanism of espin 1; hence, we investigated the interaction between actin and espin 1 through structural data. In this study, we first purified human espin 1 in an E. coli system following a new detergent-free approach and then demonstrated the 2D structure of full-length espin 1 using transmission electron microscopy along with Nickel nitrilotriacetic acid nanogold labeling and 2D averaging using SPIDER. Furthermore, we also determined the espin 1 binding domain of actin using a co-sedimentation assay along with gelsolin and myosin S1. These findings are not only beneficial for understanding the actin binding and bundling mechanism of espin 1, but also shed light on its elongation, stabilization, and tip-localization mechanisms with myosin III. This study thus provides a basis for understanding the molecular structure of espin 1 and can contribute to various hearing-related diseases, such as hearing loss and vestibular dysfunction.